Atrial fibrosis and substrate based characterization in atrial fibrillation: Time to move forwards. (17th March 2021) - Quah, Jing X.; Dharmaprani, Dhani; Tiver, Kathryn; Lahiri, Anandaroop; Hecker, Teresa; Perry, Rebecca; Selvanayagam, Joseph B.; Joseph, Majo X.; McGavigan, Andrew; Ganesan, Anand
Abstract: Atrial fibrillation (AF) is the most commonly encountered cardiac arrhythmia in clinical practice. However, current therapeutic interventions for atrial fibrillation have limited clinical efficacy as a consequence of major knowledge gaps in the mechanisms sustaining atrial fibrillation. From a mechanistic perspective, there is increasing evidence that atrial fibrosis plays a central role in the maintenance and perpetuation of atrial fibrillation. Electrophysiologically, atrial fibrosis results in alterations in conduction velocity, cellular refractoriness, and produces conduction block promoting meandering, unstable wavelets and micro‐reentrant circuits. Clinically, atrial fibrosis has also linked to poor clinical outcomes including AF‐related thromboembolic complications and arrhythmia recurrences post catheter ablation. In this article, we review the pathophysiology behind the formation of fibrosis as AF progresses, the role of fibrosis in arrhythmogenesis, surrogate markers for detection of fibrosis using cardiac magnetic resonance imaging, echocardiography and electroanatomic mapping, along with their respective limitations. We then proceed to review the current evidence behind therapeutic interventions targeting atrial fibrosis, including drugs and substrate‐based catheter ablation therapies followed by the potential future use of electro phenotyping for AF characterization to overcome the limitations of contemporary substrate‐based methodologies.